Case Report: Prone Positioning and Nasal High Flow Oxygen Therapy - An Alternative Strategy to Invasive and Non-Invasive Ventilation in a Case of Severe Acute Respiratory Distress Syndrome - Orlando Rubén Pérez Nieto; Ernesto Deloya Tomás; Karen Pamela Pozos Cortés; Jorge Hernández Zamudio; Éder Iván Zamarrón López; Raúl Soriano Orozco; Miguel Ángel Martínez Camacho; Jesús Salvador Sánchez Díaz (European Scientific Journal, ESJ, 2019)
Acute respiratory distress syndrome (ARDS) is associated with high rates of mortality, which is directly attributed to the pulmonary inflammatory response then compromising gaseous exchange. This case study describes the successful management of a 63-year-old male with severe ARDS who received a strategy which involved the following interventions: Nasal High Flow Oxygen (NHFO) therapy, and prone positioning. It is thought that this strategy improved the lung volume at end expiration to an extent that the patient was able to avoid both noninvasive (NIV) and invasive mechanical ventilation (MV) (and their known associated risks). There is limited evidence describing the use of NHF therapy in patients with ARDS. The use of prone positioning has been demonstrated to significantly improve 28-day mortality in patients with severe ARDS with a PaO2/FiO2< 150 mmHg. The authors acknowledge that until such time that controlled clinical trials considering the efficacy of strategy are conducted it would be premature to recommend it forall suchcases. The prone position is a promising therapy for patients with spontaneous ventilation with high-flow oxygen therapy; controlled and randomized studies should be done to demonstrate its safety and efficacy.